Identifying the challenges of interdisciplinary research on pornography use. Issue 5 (3rd May 2020) - Litsou, Katerina; Byron, Paul
Abstract: This paper explores some the difficulties in undertaking a large-scale systematic review of pornography research literature. Its authors come from different disciplines across the humanities and social sciences, and work within an interdisciplinary team. The research project aims to understand pornography's relationship with its audiences, particularly considering the relationship between pornography consumption and healthy sexual development. Offering a conversational account of research experiences on the project so far, the paper illustrates some key tensions and ongoing points of discussion in research committed to interdisciplinary scholarship, featuring disciplinary perspectives that do not easily correlate. We disagree on definitions, data-gathering methods and modes of data analysis. This paper does not aim to deliver solutions to these problems but presents two different voices describing our experiences of interdisciplinary porn research so far. In order to challenge and extend our disciplinary thinking, we offer an example of dialogue, and highlight the potential of listening across disciplinary frameworks. We encourage scholars from different disciplines to work together as this generates broader research perspectives and offers challenging conditions that can usefully interrogate and extend upon traditional research practice and methods. We hope this paper will generate further reflection among research peers about how best to strengthen interdisciplinary research practice, including, but not limited to, porn research.